PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH KOTA PEKANBARU DENGAN SIKAP APARAT PEMERINTAH SEBAGAI VARIABEL INTERVENING - Apriani, Aulia; Taufi, Taufeni (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
The purpose of this research is to analyze the effects of the characteristics of budgetgoals, such as: budget participation, budget goal clarity, budget feedback, budgetevaluation and the budget goal difficulty on the performance of Pekanbaru citygovernment officials and with the attitude of government officials as an interveningvariable. This research is based on samples government officialsholding mediumand lower level positions and at the same time they were the official commitmentmakersof SKPD in Pekanbaru city government. The data of this research wereanalyzed by using Structural Equation Modelling (SEM) using AMOS program. Theresults showed that: 1) budget participation has a significant effect on theperformance of government officials; 2) budget goal clarity has a significant effect onthe performance of government officials; 3) budget feedback does not significantlyinfluence the performance of government officials, 4) budget evaluation has asignificant effect on the performance of government officials, 5) budget goal difficultyhas negative influence but doesnot significantly affect the performance ofgovernment officials, 6) variable attitude capable to mediate positive to increase theinfluence of budget participation, budget goal clarity, evaluation and the budget goaldifficulty of the government official performance; 7) variable of attitude, however,cannot mediate an increase the influence of budget feedback and budget evaluationon the performance of government officials.Keywords: Budget participation, budget goal clarity, budget feedback, budgetevaluation, budget goal difficulty, performance and attitude.